Chain length variation to probe the mechanism of accelerator additives in copper electrodeposition. Issue 30 (23rd July 2019) - Schmitt, Kevin G.; Schmidt, Ralf; Gaida, Josef; Gewirth, Andrew A.
Abstract : We evaluate the effect of chain length for a series of alkyl sulfonic acid additives on Cu electrodeposition by using a combination of electrochemical and Raman spectroscopic methods. Abstract : We evaluate the effect of chain length for a series of alkyl sulfonic acid additives on Cu electrodeposition by using a combination of electrochemical and Raman spectroscopic methods. Rotating disk linear sweep voltammetry revealed the influence of these additives on the bulk concentration of Cu + and on the exchange current densities of the reduction of Cu 2+ /Cu + and Cu + /Cu. We then used in situ shell-isolated, nanoparticle-enhanced Raman spectroscopy to correlate the additives' effects on deposition kinetics with their chemical structures at the electrode surface. The combination of these methods suggests that effective Cu electrodeposition acceleration processes require: (1) direct tethering of mercaptoalkylsulfonate species to the electrode, (2) partial desolvation of Cu 2+ by the sulfonate group to minimize its solvent reorganization energy, and (3) stabilization of Cu + adjacent to the electrode surface by addition of halide. The model provides support for recently proposed theories for the electrodeposition of metals where charge is carried across the electrode interface by the cation, rather than the electron.